1999
DOI: 10.1017/s1827433100000319
|View full text |Cite
|
Sign up to set email alerts
|

Indicatori di qualità della vita

Abstract: La complessità del dibattito sulla qualità della vita si riflette nelle definizioni proposte (Oliver el al., 1996); alcune sono ampie ma vaghe, tali da non specificare il contenuto del concetto e quindi da ostacolarne la misurazione: “La qualità della vita è un ampio concetto che comprende tutti gli aspetti dell'esistenza di un individuo” (Torrance, 1987); “Nell'epoca moderna qualità della vita significa salute e benesse re, idee ampiamente comprese ed accettate dalle persone” (Oliver, 1991). Alcune definizion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The present study confirms that demographic characteristics of schizophrenia patients have a very low impact not only on total satisfaction but also on satisfaction in the various domains and that this finding is likely to have cross-cultural stability. Previous studies have found only a weak relationship between patients’ clinical characteristics, such as psychopathology or global functioning, and service satisfaction (Ruggeri et al 1998, 1999; Becker et al 1999). This study has found that higher illness severity, as measured by BPRS score, is cross-culturally associated with lower service satisfaction, especially in the domains assessing involvement of relatives and self-perceived efficacy, but the amount of variance explained is relatively low.…”
Section: Discussionmentioning
confidence: 97%
“…The present study confirms that demographic characteristics of schizophrenia patients have a very low impact not only on total satisfaction but also on satisfaction in the various domains and that this finding is likely to have cross-cultural stability. Previous studies have found only a weak relationship between patients’ clinical characteristics, such as psychopathology or global functioning, and service satisfaction (Ruggeri et al 1998, 1999; Becker et al 1999). This study has found that higher illness severity, as measured by BPRS score, is cross-culturally associated with lower service satisfaction, especially in the domains assessing involvement of relatives and self-perceived efficacy, but the amount of variance explained is relatively low.…”
Section: Discussionmentioning
confidence: 97%